Circulating liver cancer stem cells and their stemness-associated MicroRNAs as diagnostic and prognostic biomarkers for viral hepatitis-induced liver cirrhosis and hepatocellular carcinoma - Marwa Hassan; Sami Mohamed Nasr; Noha Abdelaal Amin; Eman El-Ahwany; Mona Zoheiry; Mohamed Elzallat (Non-coding RNA Research, 2023)
Background: Liver cancer stem cells (LCSCs) are a subpopulation of tumor cells that can drive cancer initiation and relapses. Because of their significance, researchers are looking for biomarkers that characterize or regulate LCSCs so that they can be used as targets for the diagnosis and treatment of chronic liver diseases and hepatocellular carcinoma (HCC). Methodology: Six groups of patients having hepatitis C virus (HCV), HCV + cirrhosis, HCV + HCC, hepatitis B virus (HBV), HBV + cirrhosis, or HBV + HCC, in addition to a control group, were subjected to the measurement of LCSCs levels and analysis of miR-1290 and miR-1825 expression. Results: The percentages of the CD133/EpCAM-expressing LCSCs were increased in viral hepatitis and cirrhosis groups, compared to the control group. HCC patients had the highest percentages of LCSCs. CD133/EpCAM-expressing cells showed significant correlations with stemness-associated miRNAs; miR-1290 and miR-1825. Also, the miR-1290 and miR-1825 were significantly up-regulated in viral hepatitis-associated cirrhosis and HCC groups. Moreover, in HCV + HCC, miR-1290 and miR-1825 expression was significantly positively correlated with tumor size and number. However, only miR-1825 could distinguish between HCV- and HBV-associated HCC groups. MiR-1290 exhibited the highest sensitivity and specificity for detecting HCC, followed by miR-1825 and CD133/EpCAM-expressing LCSCs. Conclusions: These findings indicate the relevance of CD133/EpCAM-expressing cells in the pathogenesis of liver cirrhosis and HCC developed as a consequence of either chronic HCV or HBV infection. Accordingly, CD133/EpCAM-expressing cells, miR-1290, and miR-1825, could serve as promising diagnostic and prognostic biomarkers as well as therapeutic targets in patients suffering from liver cirrhosis or HCC.